Depression among Nepalese type 2 diabetes mellitus patients and their quality of life. - Niraula, Kiran (2012)
ABSTRACT: Diabetes mellitus is frequently associated with co-morbid depression and impact upon treatment course, Prognosis which deteriorates quality of life more than by diabetes alone. The aim of the study was to assess the proportion of depression and its risk indicators and to determine association between depression and quality of life in type 2 diabetics. A cross sectional study was conduct among 385 type -2 diabetic patients attending selected tertiary centers of Kathmandu, Nepal from November, 2011 to March, 2012. Purposively selected patients diagnosed at least 3 months before were interviewed through a pretested semi-structured questionnaires. Height, weight, waist and hip circumference and blood pressure were measured following standard protocol. Data on HbA1c were collected. Depression and quality of life were measured using Nepalese versions of Beck Depression Inventory (BDI) and Audit of Diabetes Dependent Quality of Life, respectively. Mean± SD age of respondent was 51.9±13.1 years, 51.7% were females and one-third were housewives. Majorities (76%) were Hindus and lived in nuclear family (79.2%). About two- third were married, 60% were urban dwellers and 48% never attended schools. The proportion of depression was 40.3% with BDI questionnaire and 31.7% (18.7% major depression, 13.0% dysthymia) after psychiatrists ' confirmation. Depression was more common in females (OR: 2.7; 95% CI: 1.7-4.2), businessperson (OR: 4.6; 95% CI: 1.5-14.2), farmers (OR: 3.4; 95% CI: 1.2-9.4), with higher personal income (OR: 2.5; 95% CI: 1.3-4.8), men with erectile dysfunction (OR: 14. 1; 95% CI: 2.1-93.7), systolic (OR: 17.6; 95% CI: 4.8-63.8) and diastolic (OR: 13.3; 95% CI: 3.5-50.6) hypertension. Depression was associated with HbA1c ≥7 (p<0.001), diabetic complications (p<0.001), non-adherence (p<0.001), oral medication users (p<0.01), high WHR (p<0.01), longer duration of hypertension (p<0.01), longer duration of diabetes (p<0.05) and treatment (p<0.05) and high BMI (p<0.05). Total QOL scores were deteriorated with depression scores on simple linear regression analysis (r= -0.184, p<0.01). QOL domains like financial situation, work life, physical strength and leisure activity (p<0.001); drinking and eating freedom, self confidence (p<0.001); physical appearance, sex life, family and holiday (p<0.005) were significantly impaired in depressed diabetics. Depression for those with diabetes is an important co-morbidity that requires careful management because of its severe impact on treatment course, prognosis and quality of life. Concealed depression among type 2 diabetics need to assessed and managed in a diabetes care setting for good quality of life, glycemic control and treatment outcomes.